Study of Quality and Damping Factor at First and Second Resonance of Closed Organ Pipe - Adhikari, Shesh Kant (BMC Journal of Scientific Research, 2023)
The quality factor is a dimensionless physical quantity related to the damping factor present in the medium. The sound is recorded from the resonance tube experiment at the first and second resonating lengths. It is analyzed by PRAAT software to calculate the quality and damping factor. The quality factor varies from 12.50 to 146.70 and 6.32 to 130.95 at first and second resonant length respectively. In case of damping factor, it varies from 3.50x10−3 to 40.00x10−3 and 3.82 x10−3 to 79.11x10−3 at respective first and second resonating length. The ratio of the quality factor of the second resonance to that first resonance varies from 0.49 to 0.97 and for the damping factor that ratio varies from 1.02 to 2.02. The quality factor is higher at the first resonating length than at the second resonating length. The damping factor is lower in the first resonating length than in the second resonating length. From the experiment on the closed organ pipe, it was found that the system is under-damped due to the damping factor of less than one. At the first and second resonating lengths the relation between quality and damping factor is inversely nature.